An analysis of integrated child development scheme performance in contributing to alleviation of malnutrition in two economically resurgent states - Aparna Ruia; Rajul Kumar Gupta; Gargi Bandyopadhyay; Rajshree R Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: Good economic growth is considered synonymous with good nutrition. In recent past, some states (like Bihar and Gujarat) have seen unprecedented economic growth. Despite this and introducing plethora of programs (including integrated child development scheme [ICDS]) to reduce malnutrition, one state might be performing well in reducing malnutrition whereas other with equally high economic growth rate might lag behind. Is mere economic growth good enough to alleviate malnutrition? Objectives: The aim of the article is to document a critical comparative analysis of malnutrition with special emphasis on ICDS (with respect to finances, infrastructure, training, performance) in the two economically resurgent states of Gujarat and Bihar. Material and Methods: An exploratory study using secondary data sources (for ICDS performance) to critically analyze malnutrition status in Bihar and Gujarat. Results: Gujarat, which was criticized for placing excessive emphasis on economic growth, has shown sharp improvement in combating malnutrition. Undernourished children declined from 73.04% in 2007 to 25.09% in 2013, with just 1.6% being severely malnourished. On the other hand, Bihar too exhibited an impressive economic growth but still languishes at bottom with malnutrition rate of 82%. Conclusion: A high economic growth does not have automatic immediate positive gains on malnutrition alleviation.